Program Animasi Interaktif Pengenalan Tata Surya Dengan Menggunakan Adobe Flash Professional CS6 (Studi Kasus : SD Swasta Sri Pinang) - Amri Gunawan (Universitas Labuhanbatu, 2022)
Interactive learning media is a tool for the process of teaching and learning. The process is used to stimulate thoughts, feelings, attention and abilities and skills for students so as to encourage the learning process. With the advances in technology and communication science, especially in the field of computers, today’s learning media will be more easily captured and understood by students if the method used is using animation. By combining computer technology and animation, a tool to learn about the solar system is created that is difficult to understand because it is rarely found in everyday life. Children will be more difficult to capture the material if only by reading a book or listening to an explanation from the teacher, because students rarely even never see for themselves the phenomena that occur related to the solar system. With this learning media application aims to simplify the teaching and learning process and improve teaching and learning efficiency. The steps taken in the design of learning media applications are data collection activities in the form of learning materials and user interface design, with supporting software Adobe Flash Professional CS6 for media creation. The results obtained from the application of natural science learning media for elementary school students based on Adobe Flash Professional CS6 can increase student interest in learning and simplify the learning process.Interactive learning media is a tool for the process of teaching and learning. The process is used to stimulate thoughts, feelings, attention and abilities and skills for students so as to encourage the learning process. With the advances in technology and communication science, especially in the field of computers, today’s learning media will be more easily captured and understood by students if the method used is using animation. By combining computer technology and animation, a tool to learn about the solar system is created that is difficult to understand because it is rarely found in everyday life. Children will be more difficult to capture the material if only by reading a book or listening to an explanation from the teacher, because students rarely even never see for themselves the phenomena that occur related to the solar system. With this learning media application aims to simplify the teaching and learning process and improve teaching and learning efficiency. The steps taken in the design of learning media applications are data collection activities in the form of learning materials and user interface design, with supporting software Adobe Flash Professional CS6 for media creation. The results obtained from the application of natural science learning media for elementary school students based on Adobe Flash Professional CS6 can increase student interest in learning and simplify the learning process.